Perception et engagement dans l’activité d’apprentissage en contexte EMI - Annabelle Paris; Jérôme Guerin; Benoît Huet (Éducation et Socialisation)
The study presented was carried out with first-year undergraduate students in Sciences and techniques of physical and sports activities, involved in a course called EMI (English as a Medium of Instruction). The aim was to study the impact of the language of communication, English, on the experience of students during practical work. The study focused on their commitment to learning time, on the nature of what was perceived and meaningful for these students in their environment. Data analysis revealed that the modification of the communication context induced by the use of the English language led the students to pay particular attention to the information and instructions given by the trainer, as well as to the actions of their peers, particularly meaningful and significant for them. The linguistic disturbance provided by the EMI thus led the students to adapt their mode of engagement and their focalizations in the lived situations and to develop an activity of inquiry based not only on interpretations backed by the discourse but on indexical and iconic dimensions linked to the actions of peers.